Ah! Thanks, proyaop! (and Tiggsy) That makes sense. Thanks for all your help!

3 + 8(2) - 7

= 3 + 16 - 7

= 19 - 7

= 12

Hope this helped!

Thanks for all of your answers/suggestions! It helped me greatly!

Oops! I meant to say - [15/65 - 4.12/65], not −(65/15 − 65/4.12)!

We know that the cosine of A+B [cos(A + B)] is equal to -1 times cosC.

Moreover -1 times cosC is equal to cosA.cosB−sinA.sinB

Therefore,

=−(65/15−65/4.12)

= -(15 - 48) / 65 = 33/65

Hope this helped, and have a great day!